تطور الهيكل السلعي للتجارة الخارجية العربية ( 1970 – 2000 ) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
سنتناول في هذا البحث تطور التركيب السلعي للتجارة الخارجية العربية ( الصادرات + الواردات ) حيث أن تطور الهيكل السلعي للصادرات العربية يظهر سيطرة النفط على صادرات معظم الدول العربية وبالتالي فإن صادرات الدول العربية تتصف باعتمادها على سلعة أولية أو عدد محدود من المواد الأولية . و بالتالي اعتماد التنمية في هذه البلدان على حصيلة صادرات هذه المواد التي تتصف بتقلب أسعارها بشكل حاد في السوق الدولية . أما في جانب الواردات فيلاحظ استمرار النمط التقليدي للواردات العربية حيث احتلت المصنوعات ( المنسوجات و الآلات ومعدات النقل ) المرتبة الأولى في قائمة الواردات تلتها المنتجات الزراعية . وبالتالي فإن برامج الإصلاح الاقتصادي التي اتبعتها الدول العربية لم تعط ثمارها بالشكل المرجو منه حتى الآن .   We shall deal in this research with the development of commodity structure of the Arab External trade ( exports + imports ) so that the development of commodity frame of the Arabic export reveals  the influence of petroleum on the exports of most of the Arabic countries . Thus , Arabic countries exports characterize with their development on the prime  commodity or on the limited number of raw materials . Then , the dependence of advancement in these countries on the exports outcome of that materials which characterize with fluctuation of their prices sharply in the international market . According to the imports side , it is noticed then the continuation of the traditional style of Arabic imports where the products occupied ( textiles , machines , means of transportation ) the first grade in the imports list then followed by the agricultural products . Later , the programs of economical repair which the Arabic countries have followed do not give results as it is expected till now